Economic evaluation of a solar water heating system - Hawlader, Mohammad Nurul Alam; Ng, K C; Chandratilleke, T T; SHARMA, D; Koay, K H L (Pergamon, 1987)

(untitled)
This paper describes different methods of analysis of a solar water heating system to determine its economic viability. The solar fraction, required for this analysis, has been calculated with a stimulation program using hourly meteorological data of Singapore. A measured load profile, representing the average condition, was used for this program. The economic variables have been selected from the trends shown in previous years. When different economic optimization criteria were applied to the CIAS solar system, it was seen that both the life cycle saving and the annualized life cycle cost lead to the prediction of the same optimum collector area of 1200 m 2. The payback period and the internal rate of return analyses also predicted the same optimum collector area of 1000 m 2, which is smaller than that predicted by the method of life cycle costing. For the economic variables used in this analysis, the minimum payback period is about 14 years.